Interpreting Irremediability When a Mental Health Disorder is the Sole-qualifying Medical Condition for MAiD - Kirby, Jeffrey (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
In this critical commentary, a set of ethical considerations of relevance to the (currently contested) interpretation of irremediability for medical assistance in dying (MAiD) in circumstances where the sole-underlying medical condition is a mental health disorder is explored and analyzed. Based on the application of an ethics lens, a practical description of irremediability is proposed for intended use as guidance by Canadian mental health care clinicians, MAiD assessors and providers, and provincial/territorial professional regulatory authorities.